PENGARUH SIKAP DAN NORMA SUBJEKTIF TERHADAP MINAT BERWIRAUSAHA SISWA SMK IMMANUEL II - Indrawati, Sofia; Herkulana, Herkulana; Syahrud, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract This thesis entitled of "the influence of attitudes and subjective norms on entrepreneurship interest of students in class XI of vocational High School Immanuel II kec.sei raya kab.kubu raya". The problem in this research is "how the influence of attitude and subjective norm on entrepreneurship interest in the students of class XI smk Immanuel II kec.sei raya kab.kubu raya". This research uses quantitative descriptive approach. The population in this study are 158 students of class XI smk Immanuel II kec.sei raya kab.kubu raya. The samples obtained by Cluster Random Smpling technique are 114 students. Methods of data collection are interviews, questionnaires, and documentation. Methods of data analysis are descriptive analysis, linearity test, and multiple linear regression analysis.The result of research shows that: (1) there is partially influence of attitude toward entrepreneurship interest to 85,88%. (2) there is a partial effect of subjective norm to 81,70%. (3) there is influence of significance and positive simultaneous attitude and subjective norm to interest of entrepreneur 71%.Keywords: Attitudes, Subjective Norms, Entrepreneurial Interests